The reliability and validity of the Tswana translations of three pain rating scales amongst patients with back pain - Yazbek, Michelle Ann (My University, 2008)
ABSTRACT Pain is a subjective sensation and is difficult to measure. It is important to quantify pain as benefits are obtained from its quantification. The validity and reliability of pain outcome measures have been extensively researched in Europe, America and Asia. In Africa on the other hand, very few studies have been done. This study was a cross-sectional study to validate and test the reliability of pain scales.The aim of this study was to establish the validity and reliability of the Tswana translations of three pain scales, namely, the Visual Analogue scale (two versions), the Verbal Rating Scale and the Wong-Baker Faces Pain Measure. The validity of the study was determined by the face validity,criterion validity and construct validity.The statistical analysis of the results showed several significant p values (p< 0.05).However, none of the correlations illustrated a strong relationship as there were no r values in excess of 0.5 indicating a moderate correlation or greater than 0.7 indicating a good correlation. The statistical significance only indicated that the observed values were not due to chance.From the statistical analysis of the results, it became apparent that the subjects tested did not have an understanding of any of the three scales .This was seen in all the age groups and education levels selected for the purpose of this study. It is our recommendation therefore, that suitable, new scales be developed for our local population. The scales which have been used up until now are not being understood and hence are not being interpreted or used correctly in the South African context amongst Tswana speaking individuals. Future research needs to be done in developing entirely different scales for the South African scenario. More relevant and better understood scales should be developed for our local population to include persons of different languages and different education levels. This will assist in a better understanding of the health care process and will by so doing, improve their health care and management.
Keywords: pain rating; back pain; cultural differences